(untitled) - Brinkley, Captain F. (Boston, 1902)
This book introduce about early wares, wares of Hizen, wares of Satsuma, wares of Kyoto, wares of Kaga prefecture, wares of owari, or bishiu, and mino, miscellaneous wares. Modern developments of Japanese keramics.
Keywords: Nhật Bản,Japan; Lịch sử,History